2022
DOI: 10.3389/fpsyg.2022.930293
|View full text |Cite
|
Sign up to set email alerts
|

Repeating patterns: Predictive processing suggests an aesthetic learning role of the basal ganglia in repetitive stereotyped behaviors

Abstract: Recurrent, unvarying, and seemingly purposeless patterns of action and cognition are part of normal development, but also feature prominently in several neuropsychiatric conditions. Repetitive stereotyped behaviors (RSBs) can be viewed as exaggerated forms of learned habits and frequently correlate with alterations in motor, limbic, and associative basal ganglia circuits. However, it is still unclear how altered basal ganglia feedback signals actually relate to the phenomenological variability of RSBs. Why do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 221 publications
0
10
0
Order By: Relevance
“…involved in the regulation of complex behaviors; lesions in the basal ganglia region mainly result in motion abnormality (increased or decreased movements) and changes in muscle tone (increased or decreased) (40); the basal ganglia region is an important neurological area, closely related to sensory, motor, visual, and behavioral functions (13,41); in ADHD children, abnormal development of the basal ganglia region may lead to symptoms such as hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…involved in the regulation of complex behaviors; lesions in the basal ganglia region mainly result in motion abnormality (increased or decreased movements) and changes in muscle tone (increased or decreased) (40); the basal ganglia region is an important neurological area, closely related to sensory, motor, visual, and behavioral functions (13,41); in ADHD children, abnormal development of the basal ganglia region may lead to symptoms such as hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
“…The findings showed that the volume and CBF values of brain regions such as caudate nucleus, putamen, and globus pallidus were lower in ADHD children than in healthy children, suggesting abnormal development of basal ganglia brain regions in ADHD children; The basal ganglia are located in the deep brain, consisting of caudate nucleus, lenticular nucleus, putamen, globus pallidus, subthalamic nucleus and substantia nigra ( 39 ). The basal ganglia are regulated in concert with the cerebral cortex and cerebellum, and voluntary movement muscular tone and postural reflexes are also involved in the regulation of complex behaviors; lesions in the basal ganglia region mainly result in motion abnormality (increased or decreased movements) and changes in muscle tone (increased or decreased) ( 40 ); the basal ganglia region is an important neurological area, closely related to sensory, motor, visual, and behavioral functions ( 13 , 41 ); in ADHD children, abnormal development of the basal ganglia region may lead to symptoms such as hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if the task is already underway, the predictions are confirmed by the incoming sensations associated with enjoyment. This can be reinforced by other factors, such as responses of the dopaminergic system, positive affective signals, or reward signals, thereby adding more weight to the relevant action policy (Spee et al 2022). Furthermore, progress in the task may bring about incremental reconfigurations of the environment (for instance the gradual change in the shape of a Lego structure the subject is building), which in turn presents new affordances and stimulates the formulation of new predictions.…”
Section: Murray 2018mentioning
confidence: 99%
“…While such states are not exclusive to autism, and can be beneficial to the subject in certain contexts, they may also lead to inflexible behavioural patterns of fixation or perseveration that can be detrimental to task execution (Spee et al 2022;Dupuis et al 2022). In addition to continuous reselection of a particular action policy, a consequence of this selective focus can be suppression or insufficient weighting assigned to sensory or cognitive cues pertaining to other states-such as those regarding another task in need of completion.…”
Section: Murray 2018mentioning
confidence: 99%
See 1 more Smart Citation